(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
In 2020, millions of students, educators, and academic faculty (and others in the world of government, business, etc. worldwide) became aware of greater emphasis for distance teaching and learning (DTL) and communication, especially given the demands being made due to the COVID-19 pandemic. More particularly, some innovative technologies have especially been designed to bring a new coherence to the integral intersection of the teaching and learning dimensions of education, especially when focused on student-centered teaching and learning. While there may have been a grace period for educators to adjust to this paradigm shift, the online educational resources and interactive platforms for teaching science, technology, engineering, and mathematics (STEM) have made more immediate applications possible, especially given the challenges of teaching during a pandemic. The availability of technology in all academic settings, particularly STEM, has enabled educators to implement a range of diverse pedagogical approaches to engage their students more effectively in STEM learning. However, some educators lack the pedagogical skills and/or strategies needed to effectively transition to virtual/teaching online STEM topics and/or classes. The purpose of this article is to highlight the effectiveness of DTL learning by utilizing interactive websites and effectively integrating them into STEM classrooms.